Printability assessment of cement-based materials based on rheology, hydration kinetics, and viscoelastic properties. (28th March 2022) - Harbouz, Ilhame; Roziere, Emmanuel; Yahia, Ammar; Loukili, Ahmed
Highlights: Workability, Extrudability, and Buildability (WEB) requirements were linked to material properties. Restructuring parameters were suggested to assess the extrudability of cement-based materials. The influence of mix-design parameters on WEB aspects was captured. Rheology, hydration evolution, and viscoelastic properties combined to predict the printability of cement-based materials. Abstract: Designing printable cement-based materials aims to achieve targeted properties to fulfill the specific performance criteria. At fresh state, the material should satisfy particular rheological requirements to achieve a tradeoff between its workability (W), extrudability (E), and buildability (B). Given the printability criteria to be fulfilled, the selection of suitable mixture design is of the utmost importance to ensure successful 3D printing process and good structural performance, which is linked to the material's strength and stiffness properties (E, G) of the print elements. In this study, the printability of different mixtures was evaluated. The properties of the investigated mixtures were varied by mean of paste content and superplasticizer dosages (SP), viscosity-modifying admixture (VMA), and supplementary cementitious materials (SCMs). The isothermal calorimetry, static yield stress evolution, strain sweep, restructuration indices, and ultrasonic wave responses of the investigated mixtures were assessed and used to evaluate their printability. Comparison between selected material properties and printing data allowed establishing useful recommendations to select the mixture with targeted properties for successful printing and adequate structural performance.